Electron beam-plasma discharge in GDT mirror trap: experiments on plasma start-up with electron gun. (1st June 2022) - Soldatkina, E.I.; Pinzhenin, E.I.; Korobeynikova, O.A.; Maximov, V.V.; Yakovlev, D.V.; Solomakhin, A.L.; Savkin, V.Ya.; Kolesnichenko, K.S.; Ivanov, A.A.; Trunev, Yu.A.; Voskoboynikov, R.V.; Shulzhenko, G.I.; et al.
Abstract: The paper describes experiments on the injection of an electron beam into a gas at the gas dynamic trap (GDT) and develops a technique for creating a starting plasma with parameters sufficient for its subsequent heating by neutral beams. It is found that a relatively thin electron beam is capable of ionizing plasma in the entire volume of the trap, and the plasma turbulence it excites is capable of accelerating some of the electrons to energies tens of times higher than the initial energy of the beam. It is shown that, in contrast to early experiments on tabletop open traps, collective beam relaxation under GDT conditions occurs in the vicinity of the entrance magnetic mirror. Since the electron cyclotron frequency in this region significantly exceeds the plasma frequency, it is necessary to study the mechanism of a beam-plasma discharge under these conditions. As a first step along this path, we measure the radial diffusion coefficient of fast particles, as well as the rate at which they gain energy.